Cardiovascular Reactivity Accompanying Voluntary Urine Retention in Normal Young Adults (International Journal of Physiology, 2019)
BackgroundThe purpose of the present study was to observe the effect of urinary bladder distension on cardiovascular reactivity in normal young adultsMethodStudy was conducted in T.M.U Moradabad. Blood pressure and heart rate were recorded in 30 normal healthy young adults of 18–25 years of age group. Parameters were recorded in three stages (phase 1: empty bladder before drinking water, phase 2: after intake of water and with full urinary bladder, phase 3: immediately after emptying of bladder.ResultsSignificant variation (